Busbar Current Measurement with Elliptical Sensor Arrays without Conductor Specific Calibration - Weiss, Roland; Zapf, Florian; Skelly, Anna; Weigel, Robert (IEEE Transactions on Instrumentation and Measurement, 2021)
In highly efficient power electronic systems, circular arrays of magnetic field sensors offer numerous advantages compared to older magnetic core-based sensors. They feature low power consumption, low weight and a high immunity to external magnetic fields. In power converters, conductors with a rectangular cross section, a small height, and a large width are widely used. Thus, an elliptical sensor array could reduce the space needed for the current sensor e.g. in a power converter by a factor of four or more compared to a circular sensor array. In this work, we theoretically and experimentally study the sensitivity error caused by the change of the conductor geometry. Therefore, we calibrated different elliptical sensor arrays on a circular conductor and determined the sensitivity error for the use of flat conductors with different widths. This calibration on a circular conductor avoids a costly conductor specific calibration of the sensor array in the application. Two different distribution methods for elliptical sensor arrays and different ratios of the semi-axes are considered. In addition, the influence of the number of sensors and the starting position for the sensors are examined. The presented elliptical sensor arrays can be used to measure the current carried by a flat conductor largely independent of its width. For some aspect ratios, they even offer a lower sensitivity error than circular sensor arrays. In the conclusion section, design considerations for those elliptic sensor arrays are given.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Ampè re’ s law; bus bar; Calibration; circular sensor array; Conductors; contactless current measurement; Current measurement; elliptical sensor array; flat conductor; Hall effect sensors; Magnetic circuits; Magnetic cores; magnetic field sensors; Sensitivity; Sensor arrays

Crosstalk in Elliptical Sensor Arrays for Current Measurement - Zapf, Florian; Weiss, Roland; Weigel, Robert (IEEE Transactions on Instrumentation and Measurement, 2022)
Contactless current sensors that use arrays of magnetic field sensors are a good alternative to core-based current sensors because the omission of the magnetic core offers many advantages. Particularly, circular sensor arrays have proven to feature good robustness against various error sources. As rectangular bus bars are frequently used for local high-current power distribution systems, elliptic arrays would require less space than circular arrays. Up until now, no publication on magnetic interference errors of elliptic sensor arrays has been presented. This article examines the crosstalk error for different sensor distribution methods, aspect ratios, numbers of sensors, and offset angles with calculations and measurements. Therefore, an interference conductor is positioned at different angles and distances relative to the elliptic arrays. We show that the crosstalk error can be reduced with our elliptic designs in comparison to a circular design with an equal number of sensors and an equal length of the semimajor axis. The projection distribution typically offers a five times smaller crosstalk error compared to the uniform curve segment length distribution. To support the design of elliptical arrays, instructions for the optimization against interference errors for elliptic sensor arrays are given in this article. Thus, an optimal offset angle for the reduction of the crosstalk error is presented.
CRIS-Team WoS Importer:2022-04-29

Mechanically Flexible Sensor Array for Current Measurement - Zapf, Florian; Weiss, Roland; Itzke, Alexander; Gordon, Renee; Weigel, Robert (IEEE Transactions on Instrumentation and Measurement, 2020)
Contactless galvanically isolated magnetic field-based current sensors utilizing hard ferromagnetic cores are widely used in many applications, for example, power converters for drives or wind turbines. New measurement methods, e.g., circular arrays of magnetic field sensors, offer some advantages, such as low weight, mechanical flexibility, and independence of the nonlinear and hysteretic behavior of the core. Those sensor arrays can be operated in an open-loop manner or in a closed-loop manner with an additional compensation coil. The advantages of the open-loop design, which we use in this article, are lower cost, lower weight, and the opportunity to realize a mechanically flexible sensor array. In this article, we show the theoretical and experimental influence of the mechanical bending on the accuracy of circular arrays of magnetic field sensors used for current measurement. Furthermore, the inner displacement of the conductor in combination with different bendings is considered. The experimental results were taken with 12, 6, 4, and 3 Hall effect sensors that were uniformly placed on the circular array.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Conductor displacement; contactless current measurement; coreless current sensor; flexible printed circuits; Hall effect sensors; open loop; printed circuit board (PCB) bending; sensor arrays